Designing Telecollaborative Projects for Professional Communication and User Experience - Arnó-Macià, Elisabet; McCall, Mary; Kenzie, Daniel; Isohella, Suvi; Maylath, Bruce (Know-Center, 2021)
This article draws on Trans-Atlantic and Pacific Project (TAPP) collaborations (e.g., [Arnó, 14] [Vandepitte, 16]) to show how students in already-existing technical communication classes can join other classes in realistic transnational projects through ICT and thereby acquire and enhance various types of transversal competences necessary to students’ future performance in a globalized workplace.
Keywords: telecollaboration; professional communication; transversal competences; learner autonomy; usability studies; UX (User Experience); personas; fi=Viestintätieteet|en=Communication Studies|